Hands-on full stack web development with ASP.NET Core : learn end-to-end web development with leading frontend frameworks, such as Angular, React, and Vue - Dresher, Tamir; Zuker, Amir; Friedman, Shay (Packt Publishing Ltd, 2018)
In this book, you'll build a complete system with both back-end and front-end products, including ASP.NET Core, Entity Framework, TypeScript, Angular, React, Vue, and Azure. This book covers more than just implementation, as you gain additional knowledge in more relevant areas, including deployment, monitoring, and debugging.